'Disgusting, disgraceful, inconsequential and dirty renegade?': Reconstructing the early life and career of Anglo-Boer War combatant and war prisoner 'Artie' Tully, 1889-1910 - Snyders, Hendrik (Scientia Militaria - South African Journal of Military Studies, 2022)
Arthur William (‘Artie’) Tully is a largely forgotten name in South African military history. A professional boxer by trade, Australian-born Tully joined the republican forces during the South African/Anglo Boer War (1899-1902) while working on the Witwatersrand. Captured at Vaalkrantz, he became a prisoner of war on Diyatalawa in Sri Lanka (formerly Ceylon). After the Peace of Vereeniging, Tully, portrayed by his brethren as a traitor, rekindled his boxing career and established himself in Singapore, Southeast Asia, working as a bookmaker, turf commission agent and mine-owner. Tully’s visit to Australia after a thirteen-year absence was largely ignored, just like his legacy in post-war studies, and to this day, he, like thousands of others, remained an obscured figure of the Anglo-Boer/South African War. His life before the war and the factors that motivated him to join the republican cause remains unknown. For some Australians, he is an emigrant traitor of no consequence. South Africans ironically continue to celebrate the contribution of a range of other foreign participants but, for unknown reasons, continue to ignore or is blissfully unaware of the contribution of this Australian to their history. Against this background, this study reconstructed the early life and career of a significant personality with a view to end his current obscurity.